Metastatic ewing's sarcoma: Revisiting the “Evidence on the Fence” - Nehal Khanna; Avinash Pandey; Jyoti Bajpai (Indian Journal of Medical and Paediatric Oncology)
Metastatic Ewing's sarcoma is a challenging disease for oncology care providers with wide spectrum of disease at presentation, widely varying approach to the treatment and varied outcomes. The paucity of randomized evidence is a barrier in developing a consensus. This perspective provides the evidence ”for and against” the benefit of aggressive approach including local and systemic therapy in patients presenting with metastatic Ewing's sarcoma and provide general recommendations so as to help select patients who will benefit with definitive intent treatment and also, avoid aggressive approach in patients with dismal outcome.